Elevated concentrations of mercury and methylmercury in the Gadani shipbreaking area, Pakistan. (April 2021) - Kakar, Allauddin; Liem-Nguyen, Van; Mahmood, Qaisar; Jonsson, Sofi
Abstract: Gadani shipbreaking area, Pakistan, is the world's third largest shipbreaking unit. However, to date, only a few studies on the environmental impacts of the industry, including mercury (Hg) pollution, have been conducted. To address this, concentrations of total Hg (HgT) and methylmercury (MeHg) were measured in surface sediments collected from the Gadani shipbreaking area as well as a local reference area. The highest concentrations of HgT and MeHg (median ± interquartile range) were detected in samples from the beach at the yard zone (HgT: 270 ± 230 μg kg −1, MeHg: 0.65 ± 0.69 μg kg −1 ), followed by sediment samples from the inter/sub-tidal zone where ships are dismantled (HgT: 20 ± 5.8 μg kg −1, MeHg: 0.043 ± 0.016 μg kg −1 ). These concentrations were on average 4–50 and 3–30 times greater than the concentrations of HgT and MeHg, respectively, observed in the reference area. Capsule: Elevated concentrations of total and methylated mercury observed in the Gadani Shipbreaking area sediments. Graphical abstract: Unlabelled Image Highlights: Elevated concentrations of HgT and MeHg were observed in Gadani shipbreaking sediments in comparison to a local reference site. Highest concentrations of HgT and MeHg was found in the shipbreaking yards, followed by the dismantling zone Values of δ 13 C and C:N ratio observed within shipbreaking yards and dismantling zone suggests strong influence of hydrocarbons and petroleum to the organic matter composition